Adhesive film for back grinding

JP2024150706A5Active Publication Date: 2025-04-03MITSUI CHEM ICT MATERIA INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024120854
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-04-23
Filing Date
2024-07-26
Publication Date
2025-04-03
Estimated Expiration
2041-04-07

AI Technical Summary

Technical Problem

Adhesive residue often occurs on electronic components after the backgrinding process, particularly when peeling adhesive films used in dicing or stealth methods for thin electronic components.

Method used

An adhesive film comprising a base material layer and an ultraviolet curable adhesive resin layer with a breaking elongation of 20% to 200% after curing is used, which is designed to minimize residue by ensuring the film can be easily peeled off without leaving adhesive remnants.

Benefits of technology

The adhesive film effectively suppresses adhesive residue on electronic components, maintaining the integrity and cleanliness of the components during and after the backgrinding process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide an adhesive film for backgrinding capable of reducing adhesive residue on an electronic component when the adhesive film is peeled off from the electronic component after a backgrinding process.SOLUTION: An adhesive film (50) for backgrinding includes a base layer (10) and an ultraviolet-curable adhesive resin layer (20) provided on one side of the base layer (10), and is used to protect the surface of an electronic component (30), and the adhesive resin layer has a breaking elongation of 20% or more and 200% or less after ultraviolet curing.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive film for backgrinding and a method for manufacturing an electronic device. [Background technology]

[0002] 2. Description of the Related Art In the process of manufacturing electronic devices, in the step of grinding electronic components, an adhesive film is attached to the circuit-forming surface of the electronic components in order to fix the electronic components and prevent damage to the electronic components. Such adhesive films generally comprise a base film and an adhesive resin layer laminated thereon.

[0003] With the advancement of high-density mounting technology, there is a demand for thinner electronic components such as semiconductor wafers. For example, there is a demand for thinning down to a thickness of 50 μm or less. One of such thinning processes is a pre-dicing method in which a groove of a predetermined depth is formed on the surface of an electronic component before grinding the electronic component, and then the electronic component is divided into individual parts by grinding. There is also a pre-stealth method in which a laser is irradiated inside the electronic component before grinding to form a modified region, and then the electronic component is divided into individual parts by grinding.

[0004] Examples of technologies relating to adhesive films for use in such dicing-first and stealth-first methods include those described in Patent Document 1 (JP 2014-75560 A) and Patent Document 2 (JP 2016-72546 A).

[0005] Patent Document 1 describes a surface protection sheet having a pressure-sensitive adhesive layer on a substrate, which satisfies the following requirements (a) to (d). (a) The Young's modulus of the substrate is 450 MPa or more. (b) The pressure-sensitive adhesive layer has a storage modulus at 25° C. of 0.10 MPa or more. (c) the pressure-sensitive adhesive layer has a storage modulus at 50° C. of 0.20 MPa or less; (d) The thickness of the pressure-sensitive adhesive layer is 30 μm or more. Patent document 1 describes that such a surface protection sheet can prevent contamination of the protected surface of the workpiece by suppressing the infiltration of water (sludge infiltration) into the gap formed when the workpiece is split during the back grinding process.

[0006] Patent Document 2 describes an adhesive tape for protecting the surface of a semiconductor wafer, which comprises a base resin film and a radiation-curable adhesive layer formed on at least one side of the base resin film, the base resin film having at least one rigid layer having a tensile modulus of elasticity of 1 to 10 GPa, and the adhesive layer having a peel force of 0.1 to 3.0 N / 25 mm at a peel angle of 30° after radiation curing. Patent Document 2 describes that such an adhesive tape for protecting the surface of a semiconductor wafer suppresses kerf shift of individualized semiconductor chips during the back grinding process of a semiconductor wafer using the first dicing method or the first stealth method, and enables the semiconductor wafer to be processed without being damaged or contaminated. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2014-75560 A [Patent Document 2] JP 2016-72546 A Summary of the Invention [Problem to be solved by the invention]

[0008] According to the research of the present inventors, it has become clear that in the manufacturing process of electronic devices using, for example, a dicing-first method or a stealth-first method, when peeling an adhesive film from an electronic component after a backgrinding process, adhesive residue is likely to remain on the electronic component.

[0009] The present invention has been made in consideration of the above circumstances, and provides an adhesive film for backgrinding that can suppress adhesive residue on the electronic component when peeling the adhesive film from the electronic component after the backgrinding process. [Means for solving the problem]

[0010] The present inventors have conducted extensive research to achieve the above object, and have found that, in an adhesive film including a base layer and an ultraviolet-curable adhesive resin layer, by using an adhesive resin layer having a breaking elongation within a specific range after ultraviolet curing, adhesive residue on the electronic component side can be suppressed when peeling the adhesive film from the electronic component after a backgrinding process, and have completed the present invention.

[0011] According to the present invention, there are provided the following adhesive film for backgrinding and the method for producing an electronic device.

[0012] [1] A backgrinding adhesive film comprising a base layer and an ultraviolet-curable adhesive resin layer provided on one surface side of the base layer, the backgrinding adhesive film being used to protect a surface of an electronic component, The adhesive film for backgrinding, wherein the adhesive resin layer has a breaking elongation of 20% or more and 200% or less after curing with ultraviolet light. [2] In the adhesive film for backgrinding according to the above [1], The adhesive resin layer is an adhesive film for backgrinding, which contains a (meth)acrylic resin having a polymerizable carbon-carbon double bond in the molecule, and a photoinitiator. [3] In the adhesive film for backgrinding according to the above [1] or [2], The electronic component is a backgrinding adhesive film that has been half-cut or has a modified layer formed thereon. [4] In the adhesive film for backgrinding according to any one of the above [1] to [3], The adhesive film for backgrinding, wherein the thickness of the adhesive resin layer is from 10 μm to 100 μm. [5] In the adhesive film for backgrinding according to any one of the above [1] to [4], The adhesive film for backgrinding, wherein the resin constituting the base layer is one or more selected from polyolefin, polyester, polyamide, polyacrylate, polymethacrylate, polyvinyl chloride, polyvinylidene chloride, polyimide, polyetherimide, ethylene-vinyl acetate copolymer, polyacrylonitrile, polycarbonate, polystyrene, ionomer, polysulfone, polyethersulfone and polyphenylene ether. [6] A step (A) of preparing a structure including an electronic component having a circuit formation surface and an adhesive film attached to the circuit formation surface side of the electronic component; A step (B) of backgrinding a surface of the electronic component opposite to the circuit formation surface; (C) a step of removing the adhesive film from the electronic component after irradiating the adhesive film with ultraviolet light; A method for manufacturing an electronic device comprising at least A method for producing an electronic device, wherein the adhesive film is the adhesive film for backgrinding described in any one of [1] to [5] above. [7] In the method for producing an electronic device according to the above [6], The above step (A) is At least one step (A1) selected from a step (A1-1) of half-cutting the electronic component and a step (A1-2) of irradiating the electronic component with a laser to form a modified layer on the electronic component; After the step (A1), a step (A2) of attaching the adhesive film for backgrinding to the circuit-forming surface side of the electronic component; A method for manufacturing an electronic device comprising the steps of: Effect of the Invention

[0013] According to the present invention, it is possible to provide an adhesive film for backgrinding that can suppress adhesive residue on the electronic component when the adhesive film is peeled off from the electronic component after the backgrinding process. [Brief description of the drawings]

[0014] [Figure 1] 1 is a cross-sectional view showing a schematic example of a structure of an adhesive film according to an embodiment of the present invention. [Diagram 2] 1A to 1C are cross-sectional views illustrating an example of a method for manufacturing an electronic device according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, similar components are given the same reference numerals, and the description will be omitted as appropriate. In addition, the drawings are schematic diagrams and do not match the actual dimensional ratios. In addition, the numerical range "A to B" represents A or more and B or less unless otherwise specified. In addition, in this embodiment, "(meth)acrylic" means acrylic, methacrylic, or both acrylic and methacrylic.

[0016] 1. Adhesive film FIG. 1 is a cross-sectional view that illustrates an example of the structure of an adhesive film 50 according to an embodiment of the present invention. As shown in FIG. 1, the adhesive film 50 for backgrinding according to this embodiment comprises a base layer 10 and an ultraviolet-curable adhesive resin layer 20 provided on one side of the base layer 10, and is an adhesive film 50 for backgrinding used to protect the surface of an electronic component 30, and the breaking elongation of the adhesive resin layer 20 after ultraviolet curing is 20% or more and 200% or less. Here, the breaking elongation of the adhesive resin layer 20 after curing with ultraviolet light is a value measured by the following method. (method) A measurement sample is prepared by laminating an adhesive resin layer 20 of the adhesive film 50 for backgrinding according to this embodiment having a thickness, composition, etc. equivalent to that of the adhesive resin layer 20 of the adhesive film 50 for backgrinding according to this embodiment on the corona-treated surface of a corona-treated ethylene-vinyl acetate copolymer extruded film (MFR: 1.7 g / 10 min, vinyl acetate content: 9 mass%, thickness: 140 μm), and further laminating a release film (separator) such as a polyethylene terephthalate film that has been subjected to a silicone release treatment on the adhesive resin layer 20 side. Examples of the lamination method include the following methods. An adhesive resin layer 20 is formed on the release-treated surface of a silicone release-treated polyethylene terephthalate film, and then a corona-treated ethylene-vinyl acetate copolymer film is laminated onto the adhesive resin layer 20 to obtain a laminate. The resulting laminate is then heated in an oven at 40°C for 3 days to be aged. Next, the adhesive resin layer 20 of the obtained laminate was irradiated with ultraviolet light having a main wavelength of 365 nm using a high-pressure mercury lamp at an intensity of 100 mW / cm in an environment of 25°C from the ethylene-vinyl acetate copolymer film side. 2 UV radiation dose 1080mJ / cm 2 The adhesive resin layer 20 is photocured by irradiation. Next, the laminate with the photocured adhesive resin layer 20 is cut to a length of 110 mm and a width of 10 mm, and the polyethylene terephthalate film as the separator is peeled off from the laminate. Next, the adhesive resin layer 20 is chucked together with the ethylene-vinyl acetate copolymer film in a tensile tester (e.g., Shimadzu Autograph AGS-X) so that the initial chuck distance Lo is 50 mm. The sample is pulled at a speed of 30 mm / min, and the point at which breakage is visually observed in the adhesive resin layer 20 is taken as the break point, and the chuck distance at that time is taken as L. The breaking elongation (%) is calculated by (L-Lo) / Lo×100(%).

[0017] As described above, according to the research of the present inventors, it has become clear that in the manufacturing process of electronic devices using, for example, a dicing-first method or a stealth-first method, when peeling an adhesive film from an electronic component after a backgrinding process, adhesive residue is likely to remain on the electronic component. The reason for this is not clear, but it is thought that, unlike the normal backgrinding process for electronic components, it is necessary to peel off the adhesive film 50 for backgrinding from the cut electronic components, which makes it easier for glue to remain on the edges of the cut electronic components. The present inventors have conducted extensive research to achieve the above object. As a result, they have found for the first time that, in an adhesive film 50 including a base layer 10 and an ultraviolet-curable adhesive resin layer 20, by using an adhesive resin layer 20 having a breaking elongation within the above range after ultraviolet curing, it is possible to suppress adhesive residue on the electronic component 30 side when peeling the adhesive film 50 from the electronic component 30 after the back grinding process.

[0018] In the adhesive film 50 according to this embodiment, the breaking elongation of the adhesive resin layer 20 after UV curing is 20% or more and 200% or less, but from the viewpoint of designing an adhesive resin layer 20 that is less likely to leave adhesive residue by giving the adhesive resin layer 20 appropriate toughness, the breaking elongation is preferably 30% or more, more preferably 40% or more, and preferably 150% or less, more preferably 100% or less, and even more preferably 80% or less. The breaking elongation of the adhesive resin layer 20 after UV curing can be controlled within the above range, for example, by controlling the types and blending ratios of the adhesive resin, crosslinking agent, and photoinitiator that constitute the adhesive resin layer 20, and the types and content ratios of each monomer in the adhesive resin.

[0019] The overall thickness of the adhesive film 50 according to this embodiment is preferably 50 μm or more and 600 μm or less, more preferably 50 μm or more and 400 μm or less, and even more preferably 50 μm or more and 300 μm or less, in terms of the balance between mechanical properties and ease of handling.

[0020] The adhesive film 50 according to this embodiment may have other layers between each layer, such as an irregularity-absorbing resin layer, an adhesive layer, or an antistatic layer (not shown), as long as the effects of the present invention are not impaired. The irregularity-absorbing resin layer can improve the irregularity absorption of the adhesive film 50. The adhesive layer can improve the adhesion between each layer. Furthermore, the antistatic layer can improve the antistatic properties of the adhesive film 50.

[0021] The adhesive film 50 according to the present embodiment is used to protect the surface of the electronic component 30 in the manufacturing process of the electronic device, and more specifically, is used as a backgrind tape to protect the circuit-formed surface 30A (i.e., the circuit surface including the circuit pattern) of the electronic component 30 in the process of grinding the electronic component 30 (also called the backgrinding process), which is one of the manufacturing processes of the electronic device. Specifically, the adhesive film 50 is attached to the circuit-formed surface 30A of the electronic component 30 for protection, and is used in the process of grinding the surface opposite to the circuit-formed surface 30A. In particular, in the manufacturing process of the electronic device using the first dicing method, the first stealth method, etc., when the adhesive film 50 is peeled off from the electronic component 30 after the backgrinding process, adhesive residue is likely to be left on the electronic component 30 side, so the adhesive film 50 according to the present embodiment can be suitably applied to the manufacturing process of the electronic device using the first dicing method, the first stealth method, etc. Here, in the pre-dicing method, the electronic component 30 is half-cut as shown in Fig. 1. In the pre-stealth method, the electronic component 30 has a modified layer formed by laser irradiation (a region inside the electronic component 30 that has been internally processed by a laser).

[0022] Next, each layer constituting the adhesive film 50 according to this embodiment will be described.

[0023] <Base material layer> The base layer 10 is a layer provided for the purpose of improving the properties of the adhesive film 50, such as handleability, mechanical properties, and heat resistance. The base layer 10 is not particularly limited as long as it has a mechanical strength sufficient to withstand the external force applied when processing the electronic component 30, and may be, for example, a resin film. Examples of resins constituting the base layer 10 include one or more selected from polyolefins such as polyethylene, polypropylene, poly(4-methyl-1-pentene), poly(1-butene), etc.; polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.; polyamides such as nylon-6, nylon-66, polymetaxylene adipamide, etc.; (meth)acrylic resins; polyvinyl chloride; polyvinylidene chloride; polyimide; polyetherimide; ethylene-vinyl acetate copolymer; polyacrylonitrile; polycarbonate; polystyrene; ionomer; polysulfone; polyethersulfone; polyetheretherketone, etc. Among these, from the viewpoint of improving mechanical properties and transparency, one or more selected from polypropylene, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide, ethylene-vinyl acetate copolymer, and polybutylene terephthalate are preferred, and one or more selected from polyethylene terephthalate and polyethylene naphthalate are more preferred.

[0024] The substrate layer 10 may be a single layer or two or more layers. The resin film used to form the base layer 10 may be in the form of a stretched film or a film stretched in a uniaxial or biaxial direction, but from the viewpoint of improving the mechanical strength of the base layer 10, a film stretched in a uniaxial or biaxial direction is preferable. From the viewpoint of suppressing warping of electronic components after grinding, the base layer 10 is preferably one that has been annealed in advance. The base layer 10 may be surface-treated to improve adhesion to other layers. Specifically, corona treatment, plasma treatment, undercoat treatment, primer coat treatment, etc. may be performed.

[0025] From the viewpoint of obtaining good film properties, the thickness of the base layer 10 is preferably from 20 μm to 250 μm, more preferably from 30 μm to 200 μm, and even more preferably from 50 μm to 150 μm.

[0026] <Adhesive resin layer> The adhesive film 50 according to this embodiment includes an ultraviolet-curing adhesive resin layer 20 . The adhesive resin layer 20 is a layer provided on one side of the base layer 10, and is a layer that comes into contact with and adheres to the circuit-forming surface 30A of the electronic component 30 when the adhesive film 50 is attached to the circuit-forming surface 30A of the electronic component 30.

[0027] Examples of the adhesive constituting the adhesive resin layer 20 include (meth)acrylic adhesives, silicone adhesives, urethane adhesives, olefin adhesives, styrene adhesives, etc. Among these, (meth)acrylic adhesives using (meth)acrylic resins as a base polymer are preferred because the adhesive strength can be easily adjusted.

[0028] As the adhesive constituting the adhesive resin layer 20, it is preferable to use an ultraviolet crosslinking adhesive whose adhesive strength is reduced by ultraviolet light. The adhesive resin layer 20 made of an ultraviolet-crosslinking adhesive agent crosslinks when irradiated with ultraviolet light, and the adhesive strength is significantly reduced, so that the electronic component 30 can be easily peeled off from the adhesive film 50 .

[0029] Examples of the (meth)acrylic resin contained in the (meth)acrylic adhesive include a homopolymer of a (meth)acrylic acid ester compound, a copolymer of a (meth)acrylic acid ester compound and a comonomer, etc. Examples of the (meth)acrylic acid ester compound include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate. These (meth)acrylic acid ester compounds may be used alone or in combination of two or more. Examples of comonomers constituting the (meth)acrylic copolymer include vinyl acetate, (meth)acrylonitrile, styrene, (meth)acrylic acid, itaconic acid, (meth)acrylamide, methylol (meth)acrylamide, maleic anhydride, etc. These comonomers may be used alone or in combination of two or more.

[0030] Examples of ultraviolet crosslinkable (meth)acrylic adhesives include adhesives obtained by crosslinking the (meth)acrylic resin with a polymerizable carbon-carbon double bond in the molecule and a photoinitiator, and by crosslinking the (meth)acrylic resin with a crosslinking agent as required. The ultraviolet crosslinkable (meth)acrylic adhesive may further include a low molecular weight compound with two or more polymerizable carbon-carbon double bonds in the molecule.

[0031] Specifically, a (meth)acrylic resin having a polymerizable carbon-carbon double bond in the molecule is obtained as follows: First, a monomer having an ethylenic double bond and a copolymerizable monomer having a functional group (P) are copolymerized. Next, the functional group (P) contained in this copolymer is reacted with a monomer having a functional group (Q) capable of undergoing an addition reaction, a condensation reaction, or the like with the functional group (P) while leaving the double bond in the monomer, thereby introducing a polymerizable carbon-carbon double bond into the copolymer molecule.

[0032] As the monomer having an ethylenic double bond, one or more of the following may be used: alkyl acrylate and alkyl methacrylate monomers, such as methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, butyl (meth)acrylate, and ethyl (meth)acrylate; vinyl esters, such as vinyl acetate; (meth)acrylonitrile, (meth)acrylamide, and styrene; and other monomers having an ethylenic double bond.

[0033] Examples of the copolymerizable monomer having the functional group (P) include (meth)acrylic acid, maleic acid, 2-hydroxyethyl (meth)acrylate, glycidyl (meth)acrylate, N-methylol (meth)acrylamide, (meth)acryloyloxyethyl isocyanate, etc. These may be used alone or in combination of two or more. The ratio of the monomer having an ethylenic double bond to the copolymerizable monomer having a functional group (P) is preferably 70 to 99% by mass of the monomer having an ethylenic double bond and 1 to 30% by mass of the copolymerizable monomer having a functional group (P), and more preferably 80 to 95% by mass of the monomer having an ethylenic double bond and 5 to 20% by mass of the copolymerizable monomer having a functional group (P). Examples of the monomer having the functional group (Q) include the same monomers as the copolymerizable monomer having the functional group (P).

[0034] As a combination of functional group (P) and functional group (Q) to be reacted when introducing a polymerizable carbon-carbon double bond into a copolymer of a monomer having an ethylenic double bond and a copolymerizable monomer having a functional group (P), a combination that easily causes an addition reaction is preferable, such as a carboxyl group and an epoxy group, a carboxyl group and an aziridyl group, a hydroxyl group and an isocyanate group, etc. In addition to the addition reaction, any reaction that easily introduces a polymerizable carbon-carbon double bond, such as a condensation reaction between a carboxylic acid group and a hydroxyl group, may be used.

[0035] Examples of low molecular weight compounds having two or more polymerizable carbon-carbon double bonds in the molecule include tripropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetraacrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ditrimethylolpropane tetraacrylate. These may be used alone or in combination. The amount of the low molecular weight compound having two or more polymerizable carbon-carbon double bonds in the molecule is preferably 0.1 to 20 parts by mass, more preferably 5 to 18 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin.

[0036] Examples of photoinitiators include benzoin, isopropyl benzoin ether, isobutyl benzoin ether, benzophenone, Michler's ketone, chlorothioxanthone, dodecyl thioxanthone, dimethyl thioxanthone, diethyl thioxanthone, acetophenone diethyl ketal, benzyl dimethyl ketal, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 2-benzyl-2-dimethylamino-4'-morpholinobutyrophenone, 2,2-dimethoxy-2-phenylacetophenone, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)butan-1-one, etc. These may be used alone or in combination. The amount of the photoinitiator added is preferably 0.1 to 15 parts by mass, more preferably 1 to 10 parts by mass, and even more preferably 4 to 10 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin.

[0037] A crosslinking agent may be added to the ultraviolet curing adhesive. Examples of the crosslinking agent include epoxy compounds such as sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, and diglycerol polyglycidyl ether, aziridine compounds such as tetramethylolmethane-tri-β-aziridinyl propionate, trimethylolpropane-tri-β-aziridinyl propionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), and N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide), and isocyanate compounds such as tetramethylene diisocyanate, hexamethylene diisocyanate, and polyisocyanate. The ultraviolet curing adhesive may be any of a solvent type, an emulsion type, and a hot melt type.

[0038] The content of the crosslinking agent is usually preferably in a range in which the number of functional groups in the crosslinking agent is not greater than the number of functional groups in the (meth)acrylic resin, but may be excessively contained as necessary when new functional groups are generated by the crosslinking reaction or when the crosslinking reaction is slow. From the viewpoint of improving the balance between the heat resistance and adhesion of the adhesive resin layer 20, the content of the crosslinking agent in the (meth)acrylic adhesive is preferably 0.1 parts by mass or more and 15 parts by mass or less, and more preferably 0.5 parts by mass or more and 5 parts by mass or less, per 100 parts by mass of the (meth)acrylic resin.

[0039] The adhesive resin layer 20 can be formed, for example, by applying an adhesive coating liquid onto the base layer 10 . The adhesive coating liquid may be coated by a conventional coating method such as a roll coater method, a reverse roll coater method, a gravure roll method, a bar coater method, a comma coater method, or a die coater method. The conditions for drying the coated adhesive are not particularly limited, but it is generally preferable to dry the coated adhesive at a temperature range of 80 to 200°C for 10 seconds to 10 minutes. It is more preferable to dry the coated adhesive at 80 to 170°C for 15 seconds to 5 minutes. In order to sufficiently promote the crosslinking reaction between the crosslinking agent and the (meth)acrylic resin, the adhesive coating liquid may be heated at 40 to 80°C for about 5 to 300 hours after drying is completed.

[0040] In the adhesive film 50 according to the present embodiment, the thickness of the adhesive resin layer 20 is preferably 10 μm or more and 100 μm or less, more preferably 10 μm or more and 50 μm or less. When the thickness of the adhesive resin layer 20 is within the above range, a good balance between the adhesion to the surface of the electronic component 30 and the handleability is achieved.

[0041] 2. Manufacturing method of electronic device FIG. 2 is a cross-sectional view that illustrates an example of a method for manufacturing an electronic device according to an embodiment of the present invention. The method for manufacturing an electronic device according to this embodiment includes, for example, at least the following three steps. (A) A step of preparing a structure 100 including an electronic component 30 having a circuit-forming surface 30A and an adhesive film 50 attached to the circuit-forming surface 30A side of the electronic component 30. (B) a step of backgrinding a surface of the electronic component 30 opposite to the circuit formation surface 30A side; (C) A step of removing the adhesive film 50 from the electronic component 30 after irradiating the adhesive film 50 with ultraviolet light. The adhesive film 50 according to this embodiment is used as the adhesive film 50. The method for manufacturing an electronic device according to this embodiment is characterized in that the adhesive film 50 according to this embodiment is used as a so-called backgrind tape when grinding the back surface of the electronic component 30. Each step of the method for manufacturing an electronic device according to this embodiment will be described below.

[0042] (Process (A)) First, a structure 100 including an electronic component 30 having a circuit-formation surface 30A and an adhesive film 50 attached to the circuit-formation surface 30A side of the electronic component 30 is prepared. Such a structure 100 can be produced, for example, by peeling off a release film from the adhesive resin layer 20 of the adhesive film 50 to expose the surface of the adhesive resin layer 20, and attaching the circuit formation surface 30A of the electronic component 30 onto the adhesive resin layer 20.

[0043] Here, the conditions for attaching the circuit formation surface 30A of the electronic component 30 to the adhesive film 50 are not particularly limited, but may be, for example, a temperature of 20 to 80°C, a pressure of 0.05 to 0.5 MPa, and an attachment speed of 0.5 to 20 mm / sec.

[0044] It is preferable that step (A) further includes at least one step (A1) selected from step (A1-1) of half-cutting electronic component 30 and step (A1-2) of irradiating electronic component 30 with a laser to form a modified layer on electronic component 30, and step (A2) of attaching an adhesive film 50 for backgrinding to the circuit formation surface 30A side of electronic component 30 after step (A1). As described above, the adhesive film 50 according to this embodiment can be suitably used in the manufacturing process of electronic devices using a dicing-first method, a stealth-first method, etc. Therefore, a manufacturing method that performs the above-mentioned step (A1-1) which is a dicing-first method or the above-mentioned step (A1-2) which is a stealth-first method is preferable.

[0045] In step (A2), the adhesive film 50 can be heated and attached to the circuit-forming surface 30A of the electronic component 30. This makes it possible to maintain good adhesion between the adhesive resin layer 20 and the electronic component 30 for a long period of time. The heating temperature is not particularly limited, but is, for example, 60 to 80°C.

[0046] The operation of attaching the adhesive film 50 to the electronic component may be performed manually, but generally, it can be performed by a device called an automatic attachment machine equipped with a roll of adhesive film.

[0047] The electronic component 30 to be attached to the adhesive film 50 is not particularly limited, but is preferably an electronic component 30 having a circuit formation surface 30A. Examples include a semiconductor wafer, an epoxy molded wafer, a molded panel, a molded array package, a semiconductor substrate, and the like, and preferably a semiconductor wafer and an epoxy molded wafer. Examples of the semiconductor wafer include silicon wafers, sapphire wafers, germanium wafers, germanium-arsenic wafers, gallium-phosphorus wafers, gallium-arsenic-aluminum wafers, gallium-arsenic wafers, and lithium tantalate wafers, but the silicon wafer is preferably used. Examples of the epoxy mold wafer include wafers manufactured by the eWLB (Embedded Wafer Level Ball Grid Array) process, which is one of the manufacturing methods for fan-out type WLP. The semiconductor wafer and epoxy mold wafer having a circuit-forming surface are not particularly limited, but for example, the wafer may have circuits such as wiring, capacitors, diodes, transistors, etc. formed on the surface. The circuit-forming surface may be plasma-treated.

[0048] The circuit formation surface 30A of the electronic component 30 may be uneven due to the presence of bump electrodes or the like. Furthermore, the bump electrodes are bonded to electrodes formed on the mounting surface, for example, when mounting an electronic device on the mounting surface, to form an electrical connection between the electronic device and the mounting surface (the mounting surface of a printed circuit board, etc.). Examples of the bump electrode include ball bumps, printed bumps, stud bumps, plated bumps, and pillar bumps. That is, the bump electrode is usually a convex electrode. These bump electrodes may be used alone or in combination of two or more types. The height and diameter of the bump electrodes are not particularly limited, but are preferably 10 to 400 μm, more preferably 50 to 300 μm, respectively. The bump pitch is also not particularly limited, but is preferably 20 to 600 μm, more preferably 100 to 500 μm. The metal species constituting the bump electrode is not particularly limited, and examples thereof include solder, silver, gold, copper, tin, lead, bismuth, and alloys thereof, but the adhesive film 50 is preferably used when the bump electrode is a solder bump. These metal species may be used alone or in combination of two or more.

[0049] (Process (B)) Next, the surface of the electronic component 30 opposite to the circuit formation surface 30A (also called the back surface) is back-ground. Here, back grinding means thinning the electronic component to a predetermined thickness without damaging the electronic component. For example, the structure 100 is fixed to a chuck table or the like of a grinding machine, and the back surface (the surface on which no circuit is formed) of the electronic component is ground.

[0050] In such a back grinding operation, electronic component 30 is ground until its thickness becomes equal to or less than a desired thickness. The thickness of electronic component 30 before grinding is appropriately determined depending on the diameter, type, etc. of electronic component 30, and the thickness of electronic component 30 after grinding is appropriately determined depending on the size of the resulting chip, type of circuit, etc. Furthermore, when the electronic component 30 is half-cut or a modified layer is formed by laser irradiation, the electronic component 30 is divided into individual components by step (B) as shown in FIG.

[0051] The back grinding method is not particularly limited, but a known grinding method can be adopted. Each grinding can be performed while cooling the electronic component and the grindstone by pouring water on them. If necessary, a dry polishing process, which is a grinding method that does not use grinding water, can be performed at the end of the grinding process. After the back grinding is completed, chemical etching is performed as necessary. The chemical etching is performed by immersing the electronic component with the adhesive film 50 attached in an etching solution selected from the group consisting of an acidic aqueous solution consisting of a single or mixed solution of hydrofluoric acid, nitric acid, sulfuric acid, acetic acid, etc., an alkaline aqueous solution such as an aqueous potassium hydroxide solution, an aqueous sodium hydroxide solution, etc. The etching is performed for the purpose of removing distortion generated on the back surface of the electronic component, further thinning the electronic component, removing oxide films, etc., pretreatment when forming an electrode on the back surface, etc. The etching solution is appropriately selected according to the above purpose.

[0052] (Process (C)) Next, the adhesive film 50 is irradiated with ultraviolet light, and then the adhesive film 50 is removed from the electronic component 30. Before removing the adhesive film from the electronic component 30, the electronic component 30 may be mounted on a dicing tape or a dicing tape with a die attach film. The operation of removing the adhesive film 50 from the electronic component 30 may be performed manually, but can generally be performed by a device called an automatic peeling machine. The surface of the electronic component 30 after peeling off the adhesive film 50 may be washed as necessary. Examples of the washing method include wet washing such as water washing or solvent washing, and dry washing such as plasma washing. In the case of wet washing, ultrasonic washing may be used in combination. These washing methods can be appropriately selected depending on the state of contamination of the surface of the electronic component.

[0053] In step (C), the adhesive film 50 is subjected to, for example, 200 mJ / cm 2 More than 2000mJ / cm 2 The adhesive resin layer 20 is photocured by irradiating it with ultraviolet light at the following dose to reduce the adhesive strength of the adhesive resin layer 20, and then the adhesive film 50 is removed from the electronic component 30. The ultraviolet irradiation can be carried out, for example, by using ultraviolet rays having a dominant wavelength of 365 nm from a high-pressure mercury lamp. The irradiation intensity of the ultraviolet light is, for example, 50 mW / cm 2 More than 500mW / cm 2 The following is the result.

[0054] (Other processes) After steps (A) to (C) are performed, a step of mounting the obtained semiconductor chip on a circuit board may be further performed. These steps can be performed based on publicly known information.

[0055] Although the preferred embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. EXAMPLES

[0056] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited thereto. Details regarding the preparation of the adhesive film are as follows.

[0057] <Base material layer> Base layer 1: Polyethylene terephthalate film (manufactured by Toyobo Co., Ltd., product name: E7180, thickness: 50 μm, one-sided corona treatment product)

[0058] Base layer 2: Laminated film consisting of low-density polyethylene film / polyethylene terephthalate film / low-density polyethylene film (total thickness: 110 μm) A polyethylene terephthalate film (manufactured by Toray Industries, product name: Lumirror S10, thickness: 50 μm) was attached to both sides of a low-density polyethylene film (density: 0.925 kg / m 3 A corona treatment was performed on one side of the obtained laminated film.

[0059] Base layer 3: Polyethylene terephthalate film / ethylene-vinyl acetate copolymer film / acrylic film laminated film (total thickness: 145 μm) A polyethylene terephthalate film (Toyobo Co., Ltd., product name: E7180, thickness: 50 μm) and an ethylene-vinyl acetate copolymer (Mitsui Dow Polychemicals Co., Ltd., MFR: 2.5 g / 10 min) film (thickness: 70 μm) were laminated by applying a corona discharge treatment to the bonding surface of the ethylene-vinyl acetate copolymer film with the polyethylene terephthalate film. In addition, the opposite surface of the ethylene-vinyl acetate copolymer film to the polyethylene terephthalate film was also subjected to a corona discharge treatment. Next, the release surface of the release-treated polyethylene terephthalate film (separator) was coated with the following acrylic resin coating solution for substrates to a dry thickness of 20 μm, dried, and then bonded to the laminate film consisting of the above-mentioned polyethylene terephthalate film / ethylene-vinyl acetate copolymer film via the ethylene-vinyl acetate copolymer film, and aged (40°C, 3 days).The separator was then peeled off to obtain the substrate layer 3.

[0060] <Acrylic resin coating liquid for substrates> Using 0.5 parts by mass of 4,4'-azobis-4-cyanovaleric acid (Otsuka Chemical Co., Ltd., product name: ACVA) as a polymerization initiator, 74 parts by mass of butyl acrylate, 14 parts by mass of methyl methacrylate, 9 parts by mass of 2-hydroxyethyl methacrylate, 2 parts by mass of methacrylic acid, 1 part by mass of acrylamide, and 3 parts by mass of an aqueous solution of polyoxyethylene nonylpropenyl phenyl ether ammonium sulfate (Dai-ichi Kogyo Seiyaku Co., Ltd., product name: Aqualon HS-1025) were emulsion-polymerized in deionized water at 70°C for 9 hours. After the polymerization was completed, the pH was adjusted to 7 with ammonia water to obtain an aqueous acrylic polymer emulsion with a solid content concentration of 42.5%. Next, 100 parts by mass of this acrylic polymer aqueous emulsion was adjusted to pH 9 or higher using ammonia water, and 0.75 parts by mass of an aziridine-based crosslinker (ChemiTite PZ-33, manufactured by Nippon Shokubai Kagaku Kogyo Co., Ltd.) and 5 parts by mass of diethylene glycol monobutyl ether were added to obtain a coating liquid for substrates.

[0061] <(Meth)acrylic resin solution> (Meth)acrylic resin solution 1: 49 parts by mass of ethyl acrylate, 20 parts by mass of 2-ethylhexyl acrylate, 21 parts by mass of methyl acrylate, 10 parts by mass of glycidyl methacrylate, and 0.5 parts by mass of a benzoyl peroxide-based polymerization initiator as a polymerization initiator were reacted in 65 parts by mass of toluene and 50 parts by mass of ethyl acetate at 80° C. for 10 hours. After the reaction was completed, the resulting solution was cooled, and 25 parts by mass of xylene, 5 parts by mass of acrylic acid, and 0.5 parts by mass of tetradecyldimethylbenzylammonium chloride were added to the cooled solution, and the mixture was reacted at 85° C. for 32 hours while blowing in air, to obtain (meth)acrylic resin solution 1.

[0062] (Meth)acrylic resin solution 2: 77 parts by mass of n-butyl acrylate, 16 parts by mass of methyl methacrylate, 16 parts by mass of 2-hydroxyethyl acrylate, and 0.3 parts by mass of t-butylperoxy-2-ethylhexanoate as a polymerization initiator were reacted in 20 parts by mass of toluene and 80 parts by mass of ethyl acetate at 85° C. for 10 hours. After the reaction was completed, the solution was cooled, and 30 parts by mass of toluene, 7 parts by mass of methacryloyloxyethyl isocyanate (manufactured by Showa Denko, product name: Karenz MOI), and 0.05 parts by mass of dibutyltin dilaurate were added thereto, and the mixture was reacted at 85° C. for 12 hours while blowing in air, to obtain a (meth)acrylic resin solution 2.

[0063] (Meth)acrylic resin solution 3: 30 parts by mass of ethyl acrylate, 11 parts by mass of methyl acrylate, 26 parts by mass of 2-ethylhexyl acrylate, 7 parts by mass of 2-hydroxyethyl methacrylate, and 0.8 parts by mass of a benzoyl peroxide-based polymerization initiator as a polymerization initiator were reacted in 7 parts by mass of toluene and 50 parts by mass of ethyl acetate at 80° C. for 9 hours. After completion of the reaction, the resulting solution was cooled, and 25 parts by mass of toluene was added to the cooled solution to obtain (meth)acrylic resin solution 3.

[0064] <Adhesive film for evaluating breaking elongation> The additives shown in Table 1 were added to the acrylic resin solution to prepare an adhesive coating solution for the adhesive resin layer. This coating solution was applied to the release-treated surface of a silicone release-treated polyethylene terephthalate film (separator) and dried at 120°C for 3 minutes to form an adhesive resin layer with a thickness of 20 μm. Next, the corona-treated surface of a corona-treated ethylene-vinyl acetate copolymer extruded film (MFR: 1.7 g / 10 min, vinyl acetate content: 9 mass%, thickness: 140 μm) was attached to the adhesive resin layer to obtain a laminate. The obtained laminate was then heated in an oven at 40°C for 3 days to be aged.

[0065] <Adhesive film for evaluating adhesive strength and pre-dicing> The additives shown in Table 1 were added to the acrylic resin solution to prepare an adhesive coating solution for the adhesive resin layer. This coating solution was applied to a polyethylene terephthalate film (separator) that had been subjected to a silicone release treatment. Next, it was dried at 120°C for 3 minutes to form an adhesive resin layer with a thickness of 20 μm, which was then bonded to the base layer. The base layers 1 and 2 were bonded to the corona-treated surface. The separator was removed from the base layer 3, and the layer was bonded to the acrylic layer side. The resulting laminate was heated in an oven at 40°C for 3 days to mature it.

[0066] <Evaluation method> (1) Breaking elongation of adhesive resin layer after UV curing The adhesive resin layer of the ethylene-vinyl acetate copolymer extrusion film for evaluating the breaking elongation was irradiated with ultraviolet light of a main wavelength of 365 nm using a high-pressure mercury lamp at an intensity of 100 mW / cm in an environment of 25°C. 2 UV radiation dose 1080mJ / cm 2 Then, the laminate was cut to a length of 110 mm and a width of 10 mm, and the polyethylene terephthalate film serving as a separator was peeled off from the laminate. Next, the adhesive resin layer was chucked together with the ethylene-vinyl acetate copolymer extruded film in a tensile tester (Shimadzu Corporation, product name: Autograph AGS-X) so that the initial chuck distance Lo was 50 mm. The sample was pulled at a speed of 30 mm / min, and the point at which breakage was visually observed in the adhesive resin layer was taken as the break point, and the chuck distance at that time was taken as L. The breaking elongation (%) was calculated by (L-Lo) / Lo x 100 (%). Evaluation was performed with N=2, and the values ​​were averaged to obtain the measured value.

[0067] (2) Adhesive strength evaluation Substrate wafer: The mirror surface of a silicon mirror wafer (SUMCO, 4-inch single-sided mirror wafer) was ozone cleaned using a UV ozone cleaning device (Technovision, UV-208) (ozone treatment time: 60 seconds). After that, the wafer mirror surface was wiped with ethanol to prepare a substrate wafer.

[0068] Adhesion strength before UV irradiation: Under an environment of 23°C and 50% RH, the adhesive film for adhesive strength evaluation was cut to a width of 50 mm, the separator was peeled off, and the adhesive film was attached to the mirror surface of the adherend wafer via its adhesive resin layer using a hand roller, and left for 1 hour. After leaving it, one end of the adhesive film was clamped using a tensile tester (Shimadzu Corporation, product name: Autograph AGS-X), and the adhesive film was peeled off from the surface of the adherend wafer at a peel angle of 180 degrees and a peel speed of 300 mm / min. The stress at that time was measured and converted to N / 25 mm to obtain the adhesive strength. The evaluation was performed with N=2, and the values ​​were averaged to obtain the measured value. Adhesive strength after UV irradiation: In an environment of 23°C and 50% RH, the adhesive film for evaluating adhesive strength was cut to a width of 50 mm, the separator was peeled off, and the adhesive film was attached to the mirror surface of the wafer via its adhesive resin layer using a hand roller, and left for 1 hour. After leaving it, it was irradiated with UV rays with a main wavelength of 365 nm using a high-pressure mercury lamp in an environment of 25°C with an irradiation intensity of 100 mW / cm. 2 The adhesive film is exposed to 1080mJ / cm of UV light. 2After that, one end of the adhesive film was clamped using a tensile tester (Shimadzu Corporation, product name: Autograph AGS-X), and the adhesive film was peeled off from the surface of the adherend wafer at a peel angle of 180 degrees and a peel speed of 300 mm / min. The stress at that time was measured and converted to N / 25 mm to obtain the adhesive strength. The evaluation was performed with N=2, and the average value was used as the measured value.

[0069] Adhesive Residue Rating: The adherend wafer after the peeling was visually observed and evaluated according to the following criteria. 〇: No adhesive residue was found ×: Adhesive residue was observed

[0070] (3) Pre-dicing method evaluation Evaluation wafer 1: Using a dicing saw, the mirror surface of a mirror wafer (KST World Corporation, 8-inch mirror wafer, diameter: 200±0.5 mm, thickness: 725±50 μm, one-sided mirror) was half-cut to obtain evaluation wafer 1. (Blade: ZH05-SD3500-N1-70-DD, chip size: 5 mm × 8 mm, cutting depth: 58 μm, blade rotation speed: 30,000 rpm). When evaluation wafer 1 was observed with an optical microscope, the kerf width was 35 μm.

[0071] Evaluation wafer 2: Using a dicing saw, a first half cut was performed on the mirror surface of a mirror wafer (KST World Corporation, 8-inch mirror wafer, diameter: 200±0.5 mm, thickness: 725±50 μm, one-sided mirror) (blade: Z09-SD2000-Y1 58×0.25A×40×45E-L, chip size: 5 mm×8 mm, cutting depth: 15 μm, blade rotation speed: 30000 rpm). When observed with an optical microscope, the kerf width was 60 μm. Next, a second half cut was performed (blade: ZH05-SD3500-N1-70-DD, chip size: 5 mm×8 mm, cutting depth: 58 μm, blade rotation speed: 30000 rpm) to obtain evaluation wafer 2.

[0072] First dicing method: Using a tape laminator (DR3000II, manufactured by Nitto Denko Corporation), the adhesive film for pre-dicing evaluation was attached to the half-cut surface of the evaluation wafer (23° C., attachment speed: 5 mm / min, attachment pressure: 0.36 MPa). Next, the wafer was back-ground using a grinder (DISCO Corporation, DGP8760) (rough grinding and precision grinding, precision grinding amount: 40 μm, no polishing, thickness after grinding: 38 μm) and divided into individual pieces. The chipping during pre-dicing was evaluated visually after back grinding according to the following criteria. 〇: No chipping was observed, including in the triangular corners. ×: Chips were confirmed, including at the triangular corners.

[0073] Furthermore, UV irradiation and peeling of the adhesive film for pre-dicing evaluation were performed to evaluate adhesive residue after the pre-dicing method. UV irradiation was performed using a high-pressure mercury lamp at a wavelength of 365 nm and an intensity of 100 mW / cm in an environment of 25°C. 2 The amount of ultraviolet light applied to the adhesive film for dicing evaluation was 1080 mJ / cm 2 was irradiated. The adhesive film for pre-dicing evaluation was peeled off in the following manner. First, a wafer mounter (MSA300, manufactured by Nitto Denko Corporation) was used to attach a separately prepared dicing tape (used as a mounting tape) to an 8-inch wafer ring frame and the wafer side of the individualized wafer described above via the adhesive surface of the dicing tape. Next, a tape peeler (HR3000III, manufactured by Nitto Denko Corporation) was used to peel off the adhesive film for pre-dicing evaluation from the wafer notch with a peeling tape (PET38REL, manufactured by Lasting Systems Co., Ltd.). The device peelability was evaluated according to the following criteria. ○: The adhesive film for pre-dicing evaluation could be peeled off from the wafer on the first try. ×: The adhesive film for pre-dicing evaluation could not be peeled off from the wafer on the first try.

[0074] The adhesive residue on the individual wafers after the pre-dicing method was evaluated using an optical microscope (manufactured by Olympus Corporation) according to the following criteria. 〇: No adhesive residue was found ×: Adhesive residue was observed

[0075] [Example 1] To 100 parts by mass of (meth)acrylic resin solution 1 (solid content), 6.9 parts by mass of benzyl dimethyl ketal (manufactured by IGM, product name: Omnirad 651) as a photoinitiator and 0.93 parts by mass of an isocyanate-based crosslinking agent (manufactured by Mitsui Chemicals, product name: Olestar P49-75S) were added to obtain adhesive coating solution 1 for the adhesive resin layer. By the above-mentioned method, adhesive films for evaluating breaking elongation, adhesive strength, and adhesive films for evaluating pre-dicing were prepared. In addition, based on the evaluation method described above, the breaking elongation, adhesive strength, and pre-dicing method evaluations of the adhesive material after ultraviolet curing were performed. The results are shown in Table 1.

[0076] [Examples 2 to 10 and Comparative Examples 1 and 2] Each adhesive film was produced in the same manner as in Example 1, except that the types of the adhesive resin layer and the base material layer were changed to those shown in Table 1. In addition, each evaluation was performed in the same manner as in Example 1. The obtained results are shown in Table 1. The compounds listed in Table 1 are as follows: Omnirad 651 (IGM): 2,2-dimethoxy-2-phenylacetophenone Omnirad 369 (IGM): 2-benzyl-2-dimethylamino-4'-morpholinobutyrophenone Aronix M400 (manufactured by Toagosei Co., Ltd.): A mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate NK Ester AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd.): ditrimethylolpropane tetraacrylate

[0077] [Table 1]

[0078] This application claims priority based on Japanese Patent Application No. 2020-076702, filed on April 23, 2020, the disclosure of which is incorporated herein in its entirety. [Explanation of symbols]

[0079] 10 Base material layer 20 Adhesive resin layer 30 Electronic Components 30A circuit forming surface 50 Adhesive Film 100 structures

Claims

1. A backgrinding adhesive film (excluding adhesive films having the base layer, an unevenness-absorbing layer provided on one surface of the base layer, and the adhesive resin layer provided on the unevenness-absorbing layer) used to protect a surface of an electronic component, comprising: a base layer; and an ultraviolet-curable adhesive resin layer provided on one surface of the base layer; An adhesive film for backgrinding, wherein the adhesive resin layer has a breaking elongation of 20% or more and 200% or less after curing with ultraviolet light, as measured by the following method. (method) A 20 μm thick adhesive resin layer is formed on the release-treated surface of a silicone-treated polyethylene terephthalate film, and then a corona-treated ethylene-vinyl acetate copolymer film (MFR: 1.7 g / 10 min, vinyl acetate content: 9% by mass, thickness: 140 μm) is laminated onto the adhesive resin layer to obtain a laminate. The laminate is then heated in an oven at 40° C. for 3 days to be aged. The adhesive resin layer is photocured by irradiating the adhesive resin layer from the ethylene-vinyl acetate copolymer film side of the laminate with ultraviolet light having a dominant wavelength of 365 nm at an irradiation intensity of 100 mW / cm 2 and an ultraviolet amount of 1080 mJ / cm 2 using a high-pressure mercury lamp in an environment of 25° C. Next, the laminate with the photocured adhesive resin layer is cut to a length of 110 mm and a width of 10 mm, and the polyethylene terephthalate film is peeled off from the laminate. Next, the adhesive resin layer is chucked together with the ethylene-vinyl acetate copolymer film in a tensile tester so that the initial chuck distance Lo is 50 mm. The sample is pulled at a speed of 30 mm / min, and the point at which breakage is visually observed in the adhesive resin layer is taken as the break point, and the chuck distance at that time is taken as L. The breaking elongation (%) is calculated by (L-Lo) / Lo×100(%).

2. The adhesive film for backgrinding according to claim 1, The adhesive resin layer comprises a (meth)acrylic resin having a polymerizable carbon-carbon double bond in the molecule, and a photoinitiator.

3. The adhesive film for backgrinding according to claim 1 or 2, The electronic component is a half-cut adhesive film for backgrinding, or a modified layer is formed on the adhesive film.

4. The adhesive film for backgrinding according to any one of claims 1 to 3, The adhesive film for backgrinding, wherein the thickness of the adhesive resin layer is 10 μm or more and 100 μm or less.

5. The adhesive film for backgrinding according to any one of claims 1 to 4, The adhesive film for backgrinding, wherein the resin constituting the base layer contains one or more selected from polyolefin, polyester, polyamide, polyacrylate, polymethacrylate, polyvinyl chloride, polyvinylidene chloride, polyimide, polyetherimide, ethylene-vinyl acetate copolymer, polyacrylonitrile, polycarbonate, polystyrene, ionomer, polysulfone, polyethersulfone and polyphenylene ether.

6. A process (A) of preparing a structure including an electronic component having a circuit formation surface and an adhesive film attached to the circuit formation surface side of the electronic component; A step (B) of backgrinding a surface of the electronic component opposite to the circuit formation surface; (C) a step of removing the adhesive film from the electronic component after irradiating the adhesive film with ultraviolet light; The adhesive film for backgrinding according to claim 1 , which is used as the adhesive film in a manufacturing method for an electronic device comprising at least the steps of:

7. The adhesive film for backgrinding described in claim 6, wherein the step (A) includes at least one step (A1) selected from a step (A1-1) of half-cutting the electronic component and a step (A1-2) of irradiating the electronic component with a laser to form a modified layer on the electronic component.